Congenital Hypertrophic Pyloric Stenosis: A Case at the Gunung Wenang Hospital Manado - North Sulawesi Indonesia - S. M. Salendu; Abdullah B. (Paediatrica Indonesiana, 1993)
On a baby girl of 4 weeks old with the dtagnosts of congenital hypertrophic pyloric stenosis, an extremely rare case in our Hospital, surgical operation was done using the Fredet Ramsted method. The main complaint was frequent vomiting. The diagnosis was based on projectile vomiting, retarded growth, constipation, moderate dehydration and was confirmed by barium meal study. Ten days after the operation, she was discharged in a good condition.